Malaysia's Foreign Policy: The First Fifty Years: Alignment, Neutralism, Islamism by Johan Saravanamuttu, Institute of Southeast Asian Studies, 2010 - Benny Teh Cheng Guan (Kajian Malaysia, 2011)
Malaysia's foreign policy, the first fifty years: Alignment, neutralism, Islamism by Johan Saravanamuttu, Singapore: Institute of Southeast Asian Studies (ISEAS), 2010, 389 pp